Simplifying Enterprise Architecture Implementation: Integrating Lean and Agile Principles through Mini-TOGAF - Farhan Alif Budianto; Muharman Lubis; ⁠Iqbal Yulizar Mukti; Setyo Budianto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Enterprise architecture plays an important role in aligning business strategy and information technology. However, comprehensive frameworks such as TOGAF 10 are often perceived as complex due to extensive artifact requirements and high resource demands, which create challenges for organizations with limited resources. Therefore, this study aims to examine the role of lean and agile principles in simplifying enterprise architecture through the Mini-TOGAF approach to improve implementation efficiency and adaptability. This research adopts a design science research approach, focusing on the design and development of the Mini-TOGAF framework as a conceptual artifact. To establish a solid theoretical foundation and systematically define the components of Mini-TOGAF, a systematic literature review was conducted. The findings indicate that lean principles simplify enterprise architecture by eliminating waste through “just enough” documentation and by consolidating and prioritizing artifacts based on core business value. In addition, Agile principles ensure that the resulting architecture remains flexible and outcome-oriented through iterative development, rapid adaptation to change, and continuous stakeholder involvement. This study concludes that Mini-TOGAF represents a pragmatic and effective adaptation of TOGAF 10, enabling more efficient, agile, and strategically aligned enterprise architecture implementation for resource-constrained organizations.